MTMR3 risk allele enhances innate receptor-induced signaling and cytokines by decreasing autophagy and increasing caspase-1 activation - Lahiri, Amit (Proc Natl Acad Sci U S A, 2015)
Inflammatory bowel disease (IBD) is characterized by dysregulated host:microbial interactions and cytokine production. Host pattern recognition receptors (PRRs) are critical in regulating these interactions. Multiple genetic loci are associated with IBD, but altered functions for most, including in the rs713875 MTMR3/HORMAD2/LIF/OSM region, are unknown. We identified a previously undefined role for myotubularin-related protein 3 (MTMR3) in amplifying PRR-induced cytokine secretion in human macrophages and defined MTMR3-initiated mechanisms contributing to this amplification. MTMR3 decreased PRR-induced phosphatidylinositol 3-phosphate (PtdIns3P) and autophagy levels, thereby increasing PRR-induced caspase-1 activation, autocrine IL-1β secretion, NFκB signaling, and, ultimately, overall cytokine secretion. This MTMR3-mediated regulation required the N-terminal pleckstrin homology-GRAM domain and Cys413 within the phosphatase domain of MTMR3. In MTMR3-deficient macrophages, reducing the enhanced autophagy or restoring NFκB signaling rescued PRR-induced cytokines. Macrophages from rs713875 CC IBD risk carriers demonstrated increased MTMR3 expression and, in turn, decreased PRR-induced PtdIns3P and autophagy and increased PRR-induced caspase-1 activation, signaling, and cytokine secretion. Thus, the rs713875 IBD risk polymorphism increases MTMR3 expression, which modulates PRR-induced outcomes, ultimately leading to enhanced PRR-induced cytokines.